Opportunistic XOR-coding content propagation in VANET - Malakooti, H.; Jalooli, A.; Jabbarpour, M.R.; Marefat, A.; Md Noor, R. (2014)
The main difference between typical wireless networks and Vehicular Ad-hoc Networks is mostly about the way traffic is propagated in these types of networks. Unlike conventional wireless networks in VANET connections are established quick and short. Because of these two factors connections in VANET are not as reliable and robust as typical wireless networks. Hence Due to these limitations in VANET and also in order to achieve higher throughput, we are aimed at investigating the adoption of network coding with the existing data propagation and routing methods in Vehicular networks. In order to address the disadvantages, we present an approach called Opportunistic Network Coding-aware Data Dissemination in Wireless Networks (NCODWN). This approach is an enhanced version of COAR. We have managed to improve network throughput and decrease end-to-end delay of the network by implementing a more efficient and reliable mechanism. The simulation results indicate that our approach outperforms COAR in terms of end-to-end delay, percentage of encoded packets, packet delivery and network throughput.